Production Smoothness Improvement through ARENA Application in theFood Manufacturing Industry (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Improvement of manufacturing production is crucial to increase productivity. ARENA is a useful simulation application to imitate the real-time result for measuring productivity. The aim of this research is to execute production smoothness improvement through ARENA simulation application. This is a collection of production information of the selected food industry, as a real case study to construct simulation model in ARENA application. From the simulation, the current manufacturing system of the food industry will be analysed. Based on the issues found,a few improvementswere suggestedfor the system. In order to prove the enforceability of the improved system, the simulation model of the improved system is to construct and analyse its real-time performance via ARENA simulation application. Finally, the most suitable improvement suggestion will be proposed for the food industry. In conclusion, this study had implemented the ARENA application to improve the smoothness of the manufacturing system.